As dimensões da hospitalidade nas manifestações culturais do Bixiga, São Paulo/SP - BITELLI, Fábio Molinari (2017)
Considered multiethnic, the neighborhood of Bixiga is the scene of cultural manifestations that express the vitality of the use of its public space and become a tradition of the city of São Paulo. Analyzed as a place of hospitality, the public space of the neighborhood brings together three cultural manifestations of a wider group: Nossa Senhora Achiropita Party, Vai- Vai Samba School and Birthday Cake of the city of São Paulo. This study presents as general objective the analysis of such selected cultural manifestations, their aspects, dynamics and dimensions of hospitality as the sociability, reception and commensality. Characterized as a qualitative research, the methodology of oral history is used through interviews with active participants or residents of the neighborhood, observation in loco and bibliographical and documentary research. In this way, they were inventoried from the recent manifestations until the traditional ones and the delimitation of the area called Bixiga, starting from the perspective of the interviewed ones. Among the results, the vocation of the neighborhood stands out as it shelters popular and spontaneous cultural manifestations that enhance situations of belonging, sociability and host, integrating residents of the neighborhood as well as other regions.